Metastases to the craniovertebral junction: illustrative case report and review of literature - Venkatraman, Chandramouleeswaran; Lakshminarasimhan, Sindhuja; Kumar S., Pratheep; Thuvarapalayam Periasamy, Krishnaprasad (International Journal of Research in Medical Sciences, 2018)
Metastases at the craniovertebral junction represent 0.5-1% of spinal metastatic lesions. Common primary sites include breast, lung and prostate carcinoma. Initial presenting features include neck pain and occipital neuralgia. High index of suspicion is required to recognize this entity in patients presenting with neck pain. If left unrecognized, these metastatic lesions have the propensity to cause catastrophic collapse leading to significant morbidity and mortality due to fracture subluxation and spinal cord compression. Here we discuss such a patient who presented with acute onset quadriparesis and lower cranial nerve palsies due to metastatic lesion involving the C1 and C2 vertebra causing medullary and cervical cord compression. Early detection and timely intervention are key to improving outcomes in such patients.